Cost-benefit analysis of IFRS adoption: developed and emerging countries. Issue 2 (3rd October 2016) - , Shigufta Hena Uzma
Abstract : Purpose: The paper aims to build a greater understanding of countries transitioning from local generally accepted accounting principles (GAAP) to International Financial Reporting Standards (IFRS). Second, the study assembles prior literature and examines the issues raised during the convergence. Finally, the paper recognises the implications of successful convergence practices that may be useful to other emerging markets and particular reference to India which is transitioning from local GAAP to IFRS-based principles. Design/methodology/approach: The present study is a qualitative analysis that explores the Cost-benefit outcome carried by developed nations. The paper segregates the literature into three segments: developed nations, East Asian countries and the Brazil, Russia, India and China (BRIC) nations. Findings: There are numerous issues and implications divulged from studies pertaining to the adoption of IFRS, i.e. corporate governance, fair value accounting and other environmental concerns. The paper further illustrates instances of dissimilarity of the Indian Accounting Standards to the IFRS. Research limitations/implications: It is evident from the literature that limited studies have been carried out in the context of East Asian countries and BRIC nations in comparison to the developed nations. Further research should provide more comprehensive empirical evidence on the outcome of mandatory adoption of IFRS on firms in emerging countries. Originality/value: The paradigm practice of mandatory adoption of IFRS by developed nations can be an insight for emerging countries that participate in the capital markets and for companies in compliance with the IFRS.